Identification of Technical Measures That Will Simulate and Stimulate Smart Growth in A Smart Sustainable And Inclusive Digitalization - Pascal Muam MAH; Iwona SKALNA; Eric MUNYESHURI; John AKOKO; Janet OKELLO; Uwakmfon Promise OFFIONG; Victor Aghaah MAH; Nkwain Godbless NSOM (Communications of International Proceedings, 2022)
The paper identify important measures that will stimulate entrepreneurship for a smart, sustainable and inclusive economy. Modern technology has the capability to simulate and stimulate growth by harnessing and harmonizing the nation’s creativeness and innovative potential in youths. Technological tools like ICT, IoTs, Big data and cloud computing skills are specifically needed for consumer needs in a smart productive system. In our today’s world of Digital economy that has generate new functions for our society and most importantly on old theories that were built on non-digital platform standards has not really fit in to the smart systems.. This study identify areas that restructuring, should include such as 1) smart future tools, 2) smart future systems and 3) smart future strategies. The study aim is to see more machines to man than more men to machine as a future tool, system of the future and strategy of the future that enhance quality consumer pattern. A survey was carried out with a set of questionnaires to determine the desires of general public. Result show high expectation amongst respondents. From the survey, the paper suggest an innovative model on how identify areas that restructuring should include as identify by the paper such as, smart future tools, smart systems of the future and smart future strategy can be implemented.
Keywords: smart Inclusive digitalization; Smart economy; smart sustainable growth; smart strategies; Technological tools